Everyone already has their community beyond the screen: Reconceptualising learning and expanding boundaries - Lee, Kyungmee (Proceedings of the International Conference on Networked Learning, 2018)
Under a prominent recent regime of online education, often represented in the scholarship as a “social constructive learning paradigm”, learning is defined as a social practice that involves a group of students actively participating in collaborative knowledge construction processes. Pedagogical theories and strategies developed and utilised in that regime focus extensively on enabling student-to-student interaction and building communities of learners in online learning environments. In this context, where the notions of “collaborative” learning and learning “community” have gained substantial legitimacy from relevant theoretical traditions, other beliefs about meaningful learning are likely to be harshly criticised or, at best, simply neglected. However, it is not at all difficult to notice a gap between the accepted theoretical ideas of effective online learning and actual pedagogical practices in most online education institutions. Here, I aim to reduce that theory-practice gap by reconceptualising online learning using a double-layered Community of Practice (CoP) model. That module conceptualises online learning as interlinked processes of participation and socialisation in multiple communities across internal and external or online and offline “layers” of learners’ lives. The model helps online course designers and instructors to expand the boundaries of their course environments or designs to reach out to students’ personal and professional lives and to make sense of online learning experiences that are shaped by their interactions with other members of different communities outside the course environments. Using data, three students’ narratives, collected from a series of case studies on learners’ learning experiences in three different types of online courses (or programmes), this article effectively demonstrates how difficult it is to develop a strong CoP nested and sustained within online learning environments, which usually have a close finish. The article further argues that it may be useful for instructional designers to expend their view on learning environment to include distance learners’ life situations beyond their computer screens. Everyone has their own community in which they naturally learn, develop, and live with other members outside the courses. Thus, rather than putting so much effort to form a community inside our learning environment, we may want to think about more effectively support our students to form a stronger and more sustainable community in their lives through being engaged in learning activities in our course.